Metabolical shifts towards alternative BTEX biodegradation intermediates induced by perfluorinated compounds in firefighting foams - Montagnolli, Renato Nallin [UNESP]; Lopes, Paulo Renato Matos [UNESP]; Cruz, Jaqueline Matos [UNESP]; Claro, Marina Turini [UNESP]; Quiterio, Gabriela Mercuri [UNESP]; Bidoia, Ederio Dino [UNESP] (Elsevier, 2017)
The type and concentration of perfluorinated compounds (PFCs) can induce different types of enzymes and promote alternate patterns of BTEX transformation. However, it is not known how the presence of active fluorocarbon-degrading microbial populations affects the transformation of BTEX. In addition to chemical analysis at the molecular level, our research approached the aqueous film forming fire-fighting foams (AFFF) and BTEX co-contamination at a large-scale with respirometers to quantify the total microbial metabolism of soil via CO2output levels. The intended outcome of this research was to obtain and characterize shifts in BTEX degradation at a set realistic environmental condition while measuring byproducts and CO2production. Both methodologies complimentarily provided an in-depth knowledge of the environmental behavior of fire-fighting foams. The biodegradation was monitored using headspace sampling and two types of gas chromatography: thermal conductivity detector and flame ionization detector. Headspace samples were periodically withdrawn for BTEX biodegradation and CO2production analysis. Our research suggests the discovery of an altered metabolic pathway in aromatic hydrocarbons biodegradation that is directly affected by fluorinated substances. The fluorinated compounds affected the BTEX biodegradation kinetics, as PFCs may contribute to a shift in styrene and catechol concentrations in co-contamination scenarios. A faster production of styrene and catechol was detected. Catechol is also rapidly consumed, thus undergoing further metabolic stages earlier under the presence of PFCs. The release of AFFF compounds not only changes byproducts output but also drastically disturbs the soil microbiota according to the highly variable CO2yields. Therefore, we observed a high sensitivity of microbial consortia due to PFCs in the AFFF formulation, therefore shifting their BTEX degradation routes in terms of intermediate products concentration.
Keywords: AFFF; Catechol; Gas-chomatrography; Respirometry; Styrene